Douglas, you're a genius! - Adamson, Ged (Schwartz & Wade Books, 2018)
Nancy and Douglas, determined to learn what is on the other side of a fence, try Nancy's plans to launch, vault, and fly Douglas over, then succeed with Douglas's simple idea.